EU scenarios of renewable coal hydro-gasification for SNG production. (August 2016) - Tosti, Silvano; Spazzafumo, Giuseppe; Capobianco, Damiano; Buceti, Giuliano; Pozio, Alfonso; Bartucca, Silvia
Abstract: The competitiveness of the substitute natural gas (SNG) production via hydrogasification of coal strongly depends on the availability of low-cost hydrogen. Today this could be obtained by renewable sources, particularly wind and solar, when energy production exceeds consumption (off-peak hours). In fact SNG not only can be considered as an attractive, versatile energy carrier for coal, but also can be used for storage of surplus power from renewables, promoting their penetration in the future energy systems. In this work, hydro-gasification processes are therefore evaluated as a novel option for the energy policy of the European Union (EU). The results of a process simulation on samples of European coals have been used to assess the energy and exergy efficiencies of the specific case studies. Particularly, this work shows that in EU the production of up to 100 × 10 9  N m 3 of natural gas via coal hydro-gasification is achievable in a near future by requiring only a further acceleration of wind power investments. Such an energy policy could reduce significantly the EU imports of natural gas, develop the flexibility and competitiveness of the energy market and promote the deployment of clean and sustainable energy technologies.